Enterotoxemia Caused by Clostridium perfringens Type E in a Calf - Eroksuz, Yesari; Otlu, Bads; Calicioglu, Mehmet; Eroksuz, Hatice; Incili, Canan Akdeniz; Karabulut, Burak; Abayli, Hasan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2018)
Clostridial enterotoxemia caused by Clostridium perfringens type E was diagnosed postmortem in a 2-months-old calf in a family farm containing 20 cattle at different ages. Varying degrees of severity of segmental fibrino-hemorrhagic and necrotic enteritis was present at the necropsy. Clostridium perfringens was isolated from the intestinal tissue and intestinal content and the genes encoding alpha and iota toxins were detected by polymerase chain reaction (PCR). Histopathological examination showed the presence of adherent Gram-positive rods on the surface of villi and in poly morphonuclear leucocytes in the lamina propria of the intestinal mucosa.Overall, the results of the present study suggest that C. perfringens type E should be considered at differential diagnosis in fibrino-hemorrhagic enteritis and sudden deaths in post weaned calves.
Bir buzağıda clostridium perfringens tip e nedenli enterotoksemi olgusu
Keywords: Bovine; Clostridium perfringens type E; Enterotoxemia